Development of carboxymethyl cellulose based proton conducting biopolymer electrolytes and its application in solid-state proton battery - Ahmad Salihin Samsudin (Terengganu: Universiti Malaysia Terengganu, 2016)
The chronicle in the field of alternative energy for energy storage has shown an excellent progress for the past few years. The increasing interest in green energy storage materials with the development of polymer or biopolymer as electrolytes candidate has attracted great attention.